Evaluation of IL-17 Producing Memory Regulatory and Effector T Cells Expressing CD26 Molecule in Patients with Psoriasis - Behnaz Esmaeili; Parvin Mansouri; Alipasha Meysamie; Maryam Izad (Iranian Journal of Allergy, Asthma and Immunology, 2018)
Memory regulatory T cells (Tregs) has been demonstrated to produce IL-17 in Psoriasis. Forkhead box P3 (Foxp3) has been demonstrated not to be reliable marker to evaluate Treg cells. Effector CD4+T cells also express Foxp3 after activation. Human T helper-17 cells (Th-17) express high level of surface CD26, while regulatory T cells are CD26 negative or low and this phenotype is stable even after activation of Treg cells. In this study, we aimed to analyze IL-17 producing Treg cells using CD26. Memory T cells were isolated from 10 patients with psoriasis and 10 controls. Ex vivo stimulated IL-17 producing regulatory (Forkhead Box P3 (Foxp3)+CD25+CD26-/low) and effector (Foxp3+CD25+CD26hi) memory T cells were analyzed by flow cytometry. IL-23, IL-6, TNFα, TGFβ and IL-17 cytokine levels were also evaluated. No significant difference in IL-17+memory regulatory T cells was seen between patients and controls (p=0.19). A significant decrease in the percentage of IL-17 producing CD26hi effector memory T cells was observed in patients (p=0.04). However, the percentage of these cells was not different between patients with mild or severe form of psoriasis compared to controls (p=0.13). We could not find any significant difference regarding IL-23, IL-6, TNFα, TGFβ and IL-17 cytokine levels in plasma and cell culture supernatant samples between patients and controls. Taken together, our results showed a reduced IL-17 producing effector memory CD26hi T cells in patients with psoriasis compared to controls. However, IL-17 producing memory regulatory CD4+T cells of patients showed no significant difference from that of controls.